Adaptation of new technologies for operation of a demonstrative module for tilapia culture in La Libertad (Scientia Agropecuaria, 2016)
The study was performed in order to identify the feasibility of operating a demonstration module production seed Nile tilapia in La Libertad. They told rearing tanks with aeration system and water recirculation supplemented with probiotic administration. Brood fish were acquired in Moyobamba, San Martin and after receipt underwent a selection process based on morphological characteristics that offer advantage for meat production. In breeding adults was established relationship female male 3: 1. They were examined periodically females to collect eggs or larvae in their mouth for handling in artisanal incubators. They were evaluated the physical and chemical variables units incubation and breeding for the purpose of monitoring and control of water quality observing demonstration module temperature levels of 16.6 and 29 °C without the survival of being affected species. The highest frequency of spawning occurred in the summer season with temperature levels of 29 °C making the extraction and incubation of 4900 eggs in artisanal incubators determining a production of 3932 juvenile fish with a survival of 80.8%. The module operation seed production was technically feasible for Nile tilapia in La Libertad.
Keywords: Nilotic Tilapia; module of seed production